2015
DOI: 10.1175/jas-d-14-0044.1
|View full text |Cite
|
Sign up to set email alerts
|

Why Do Model Tropical Cyclones Intensify More Rapidly at Low Latitudes?

Abstract: The authors examine the problem of why model tropical cyclones intensify more rapidly at low latitudes. The answer to this question touches on practically all facets of the dynamics and thermodynamics of tropical cyclones. The answer invokes the conventional spin-up mechanism, as articulated in classical and recent work, together with a boundary layer feedback mechanism linking the strength of the boundary layer inflow to that of the diabatic forcing of the meridional overturning circulation.The specific role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 55 publications
(70 reference statements)
2
43
0
Order By: Relevance
“…−( u / r ) ∂M / ∂r ), the reduction of the magnitude of inflow (i.e of − u ) is to some extent mitigated by the increase in the magnitude of ∂M / ∂r and again one cannot anticipate the change in ∂v / ∂ta priori : one has to perform the calculation (e.g. Smith et al , ).…”
Section: Idealized Symmetric Modelsmentioning
confidence: 99%
“…−( u / r ) ∂M / ∂r ), the reduction of the magnitude of inflow (i.e of − u ) is to some extent mitigated by the increase in the magnitude of ∂M / ∂r and again one cannot anticipate the change in ∂v / ∂ta priori : one has to perform the calculation (e.g. Smith et al , ).…”
Section: Idealized Symmetric Modelsmentioning
confidence: 99%
“…In addition, they did not mention the differences in the strength of the convective forcing, which, as we will show here, are fundamental to understanding these effects. Indeed, Smith et al (2015) showed that the convective forcing is paramount and that inertial stability (above the boundary layer) plays a minor role, certainly on the intensification at different latitudes. They showed also that the boundary layer has a strong control on the location and strength of the convective forcing as the latitude is varied.…”
Section: Introductionmentioning
confidence: 99%
“…By itself, the Q pattern (Figure 2c) suggests an annular eyewall with a localized heating pattern extending through the troposphere and sloping outwards. However, at this early stage of development, the convection exhibits a high degree of asymmetry and the Q pattern comes from vertically coherent vortical plumes [11,31]. The F λ field (Figure 2d) exhibits a more complex pattern.…”
Section: Resultsmentioning
confidence: 96%